Speaker, audience and situations - Hester, J. D. (1998)
In his paper 'Toward an interactional model for the analysis of Letters' (Neat 24, 1990). Johannes Vorster develops an interpretive model based on a synthesis of aspects of communication theory, speech act theory, conversational analysis and classical status theory. This paper offers a different perspective on the concept of the particular and universal audience, and develops a different synthesis in order to contribute to rhetorical criticism of the Letters and not just analysis.
Keywords: Vorster; J.N; Speech Act Theory; Conversational analysis; Communication Theory; Classical status theory; Hermeneutics; Theology; Christianity